Learning Journal: Improving Teaching Strategies Through Students’ Reflections - Fajriah, Fajriah (Yayasan Sukma, 2017)
This study is concerned with how teachers use students’ reflections to improve their teaching strategies. The purpose of this study was to explore the role of students’ reflections in the learning process, and how the teachers use those reflections to improve teaching strategies. This research used a qualitative approach.The results of the study indicated that the role of students’ journals in learning was to know students’ points of view and to explore students’ needs. In addition, the ways the teachers improved were by changing their teaching methods and changing their attitudes. Therefore, it was considered that the teachers were able to develop their pedagogical competence. Additionally, the students remarked that a good relationship with the teacher is more important than a good teaching strategy.[Artikel ini membahas strategi guru menggunakan umpan balik dari siswa untuk memperbaiki strategi pengajaran. Tujuan dari penelitian ini adalah untuk mengeksplorasi peran umpan balik siswa dalam proses pembelajaran dan penggunaannya untuk memperbaiki strategi pengajaran. Hasil penelitian menunjukkan bahwa jurnal siswa dalam pembelajaran berfungsi untuk mengetahui sudut pandang siswa dan untuk mengeksplorasi kebutuhan siswa. Dengan dasar itulah para guru dapat memperbaiki metode dan sikap dalam proses pengajaran, sehingga dapat mengembangkan kompetensi pedagogis mereka. Selain itu, bagi siswa, hubungan yang baik dengan guru lebih berpengaruh daripada strategi pengajaran.]